Urinary incontinence: prevalence, need for treatment, and effectiveness of intervention by nurse. Issue 6813 (23rd November 1991) - O'Brien, J; Austin, M; Sethi, P; O'Boyle, P
Abstract : OBJECTIVE--To measure the unmet need of patients with regular urinary incontinence (incontinence twice or more a month) treatable by a nurse. DESIGN--Self completed postal questionnaire and randomised controlled trial of assessment and intervention by a nurse. SETTING--One urban and one rural general practice in Somerset. SUBJECTS--7300 adults randomly selected from 10, 300 aged 35 and over on the combined practice lists. 515 women and 185 men with regular incontinence were offered assessment and treatment, of whom 134 women and 49 men had no intervention for three months (historical controls). They then joined the assessment and treatment programme. INTERVENTION--Four sessions of pelvic floor exercises and bladder retraining supervised by non-specialist nurse who had taken a three week course on assessing and treating uncomplicated incontinence. MAIN OUTCOME MEASURES--Number of patients desiring treatment; self reported cure, improvement, or deterioration in continence after three months. RESULTS--The questionnaire achieved a 79% response. Validated responses showed a prevalence of 4.4% in men and 16.4% in women aged 35-64. 315 (45%) of the 700 patients offered assessment refused it and seven had moved away or died, 64 men and 41 women were referred to their general practitioner. 197 of 292 treated women (68%) reported cure or improvement compared with seven (5%) of controls. 22 of the 86 men desiring treatment were suitable for intervention by the nurse. Seventeen were cured or improved compared with none of the men in the control group. CONCLUSIONS--About half the people with regular urinary incontinence took up the offer of treatment (9.2% of women and 3.4% of men in the study population). This condition can be effectively managed by a nurse with limited training.